Clinical impact of air pollution on SPECT myocardial perfusion imaging - Océane Bouchot; Stephan Gabet; Loïc Djaileb; Aurélia Robin; Nicolas De Leiris; Julie Roux; Laurent Riou; Gerald Vanzetto; Daniel Fagret; Catherine Ghezzi; Rémy Slama; Gilles Barone-Rochette (Environment International)
Background: Air pollution contributes to cardiovascular morbimortality. Air pollution effects on cardiovascular function assessed from non-invasive and invasive imaging have been reported but never on myocardial perfusion. This study aimed to characterize relations of air pollution exposure to myocardial perfusion imaging (MPI). Methods: Patients referred to SPECT (single-photon emission computed tomography) MPI were prospectively enrolled between 2017 and 2020. Myocardial ischemia was assessed from the SPECT. Moderate-to-severe ischemia was defined as a > 10 % ischemic myocardium. Exposures to particulate matter (PM2.5 and PM10) and NO2 at the home address were characterized via a 10-meter resolution air pollutant-dispersion model and air quality monitoring system data. Associations of exposures with scintigraphy parameters were assessed through multivariable regressions, and potential modifying effects by sex and BMI were investigated. Results: A total of 1,585 participants were prospectively included (mean age 67.7 ± 11.6 years, 63.3 % male); 148 (9.3 %) patients presented a moderate-to-severe ischemia. In multivariate analysis, the odds of moderate-to-severe ischemia was increased, with adjusted odds-ratio (ORa) of 1.39 [95 % confidence interval (95 % CI): 1.07–1.80; p = 0.013], 1.33 (95 % CI: 1.01–1.75; p = 0.042), and 1.22 (95 % CI: 0.96–1.57; p = 0.10) for each increase of one Interquartile Range (IQR) in PM2.5, PM10 and NO2 exposure, respectively (IQR equal to 3.3, 4.3 and 10.0 µg/m3, respectively). With further adjustment for cardiometabolic diseases and symptoms, only the association with PM2.5 remained statistically significant: ORa 1.34 (95 % CI: 1.03–1.75, p = 0.031) for each one-IQR increase. Associations with PM10 and PM2.5 tended to be stronger in women (interaction p-value equal to 0.11 and 0.077, respectively). Conclusion: We provide new insights into a mechanism by which particulate air pollution may influence cardiovascular risk. Exposure to PM was associated with moderate-to-severe ischemia, particularly in women.